Would I ever lie to you? - Buehner, Caralyn (Dial Books for Young Readers, 2007)
A young boy is never sure if his older cousin is teasing or telling the truth. When your cousin is always telling outrageous tales, how do you know what to believe? He says you were hatched from an egg in the garden, and that sure sounds absurd. But not all of his stories are false: He was right about your aunt Mary not having teeth; and Dad agreed with him that, yes, your mom does have eyes in the back of her head! So when Ed tells you that your dessert - the piece of pie you've been looking forward to all meal long - is full of poison, what should you do?